Epithelial cell‐expressed type II IL‐4 receptor mediates eosinophilic esophagitis. Issue 2 (13th September 2022) - Avlas, Shmulik; Shani, Guy; Rhone, Natalie; Itan, Michal; Dolitzky, Avishay; Hazut, Inbal; Grisaru‐Tal, Sharon; Gordon, Yaara; Shoda, Tetsuo; Ballaban, Adina; Ben‐Baruch, Netali Morgenstern; Rochman, Mark; et al.
Abstract: Background: Eosinophilic esophagitis (EoE) is a chronic, food‐driven allergic disease, characterized by eosinophil‐rich inflammation in the esophagus. The histopathological and clinical features of EoE have been attributed to overproduction of the type 2 cytokines IL‐4 and IL‐13, which mediate profound alterations in the esophageal epithelium and neutralizing of their shared receptor component (IL‐4Rα) with a human antibody drug (dupilumab) demonstrates clinical efficacy. Yet, the relative contribution of IL‐4 and IL‐13 and whether the type II IL‐4 receptor (comprised of the IL‐4Rα chain in association with IL‐13Rα1) mediates this effect has not been determined. Methods: Experimental EoE was induced in WT, Il13ra1 −/−, and Krt14 Cre /Il13ra1 fl/fl mice by skin‐sensitized using 4‐ethoxymethylene‐2‐phenyl‐2‐oxazolin (OXA) followed by intraesophageal challenges. Esophageal histopathology was determined histologically. RNA was extracted and sequenced for transcriptome analysis and compared with human EoE RNAseq data. Results: Induction of experimental EoE in mice lacking Il13ra1 and in vivo IL‐13 antibody‐based neutralization experiments blocked antigen‐induced esophageal epithelial and lamina propria thickening, basal cell proliferation, eosinophilia, and tissue remodeling. In vivo targeted deletion of Il13ra1 in esophageal epithelial cells rendered mice protected from experimental EoE. Single‐cell RNA sequencing analysis of human EoE biopsies revealed predominant expression of IL‐13Rα1 in epithelial cells and that EoE signature genes correlated with IL‐13 expression compared with IL‐4. Conclusions: We demonstrate a definitive role for IL‐13 signaling via IL‐13Rα1 in EoE. These data provide mechanistic insights into the mode of action of current therapies in EoE and highlight the type II IL‐4R as a future therapeutic target. Abstract : This study described the development of an experimental model for EoE using skin sensitization followed by intraesophageal challenges of oxazolone. Experimental EoE recapitulates the major clinical features of human disease, including epithelial cell proliferation, intraepithelial eosinophilia, fibrosis, and marked transcriptional resemblance to human EoE. Il13ra1 −/− mice are completely protected from EoE demonstrating that the type 2 IL‐4 receptor (i.e., IL‐13Rα1) has a critical role in the pathogenesis of EoE.Abbreviations: EoE, eosinophilic esophagitis; IL‐4Rα, interleukin 4 receptor α; IL‐13α1, interleukin 13 receptor α1; JAK, Janus kinase